Modelling of low-velocity impacts on composite beams in large displacement - M. Utzeri; M. Sasso; G. Chiappini; S. Lenci (Fracture and Structural Integrity)
The paper provides an evaluation of the nonlinear dynamic response of a cantilever beam made of composite material subjected to low-velocity impacts. The structure is assumed to respond in a quasi-static manner and modelled by a continuous beam in large displacement with a lumped mass attached. First, an analytical model was developed to study the free vibrations of a beam, taking into account the nonlinearities due to large displacements and inertia. Then, the analytical findings were compared with experimental test data. The vibration of a real composite beam has been acquired through high-speed imaging technique. The displacements of the beam were extracted by digital image analysis; then, the nonlinear parameters of the analytical model were determined by the Fitting Time History technique. The results obtained by the analytical model and the experimental test are compared with numerical analysis. The validated analytical model was adapted to study a low-velocity impact; the lumped mass was associated with a rigid projectile, whose initial speed represents the impact velocity